The Government's Responsibility in Providing Compensation and Restitution in the Perspective of the Legal Theory of Dignified Justice - Hamamah, Fatin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The principle of legal equality is one of the characteristics of a rule of law state, victims of criminal justice must receive guaranteed legal protection. The position of the victim in the criminal justice system is still neglected because Indonesian criminal law is still oriented towards the interests of the perpetrator (Offer Oriented). Existing compensation and restitution arrangements are not in favor of victims of criminal acts.Purposes of the Research: The purpose of this research is to analyze compensation and restitution in the perspective of the Legal Theory of Dignified Justice.Methods of the Research: The research method used is a normative approach based on the philosophy of Pancasila.Results of the Research: Compensation and restitution arrangements in positive law are still not synergized well, so it is necessary to make legal policies related to the implementation of restitution for victims of criminal acts based on the values and legal culture of society. In the perspective of the theory of an integrated criminal justice system, the disharmony of legal substance and the asymmetry of the legal structure must be addressed immediately. The government must be held responsible for criminal acts if it is unable to pay restitution to victims of criminal acts. There is a need to improve compensation and restitution arrangements so that they are more pro-victims of crime and in accordance with the values and legal culture of society.